The Exploration of Effects of Chinese Cultural Values on the Attitudes and Behaviors of Chinese Restaurateurs Toward Food Safety Training - Liu, Pei; Kwon, Junehee (My University, 2016)
Foodborne illness is a challenge in the production and service of ethnic foods. The purpose of the study described in this article was to explore variables influencing the behaviors of U.S. Chinese restaurant owners/operators regarding the provision of food safety training in their restaurants. Seventeen major Chinese cultural values were identified through individual interviews with 20 Chinese restaurant owners/operators. Most participants felt satisfied with their previous health inspections. Several expressed having difficulty, however, following the health inspectors’ instructions and in understanding the health inspection report. A few participants provided food safety training to their employees due to state law. Lack of money, time, labor/energy, and a perceived need for food safety training were recognized as major challenges to providing food safety training in Chinese restaurants. Videos, case studies, and food safety training handbooks were the most preferred food safety training methods of Chinese restaurant owners/operators, and Chinese was the preferred language in which to conduct the training.
Citation: Liu, P., & Kwon, J. (2013). The exploration of effects of Chinese cultural values on the attitudes and behaviors of Chinese restaurateurs toward food safety training. Journal of Environmental Health, 75(10), 38-46.